Tìm x, biết:
a) (3x – 5)2 – (x +1 )2 = 0
b) (5x – 4)2 – 49x2 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,x(x-2)+x-2=0
⇔ (x-2)(x+1)=0
⇔ x=2;x=-1
b,x3+x2+x+1=0
⇔ x2(x+1)+x+1=0
⇔ (x+1)(x2+1)=0
⇔ x=-1
a) Ta có: \(7x^2-28=0\)
\(\Leftrightarrow7\left(x^2-4\right)=0\)
\(\Leftrightarrow7\left(x-2\right)\left(x+2\right)=0\)
mà 7>0
nên (x-2)(x+2)=0
hay \(\left[{}\begin{matrix}x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\)
Vậy: \(x\in\left\{2;-2\right\}\)
b) Ta có: \(\dfrac{2}{3}x\left(x^2-4\right)=0\)
\(\Leftrightarrow\dfrac{2}{3}x\left(x-2\right)\left(x+2\right)=0\)
mà \(\dfrac{2}{3}>0\)
nên x(x-2)(x+2)=0
hay \(\left[{}\begin{matrix}x=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\\x=-2\end{matrix}\right.\)
Vậy: \(x\in\left\{0;-2;2\right\}\)
c) Ta có: \(2x\left(3x-5\right)-\left(5-3x\right)=0\)
\(\Leftrightarrow2x\left(3x-5\right)+\left(3x-5\right)=0\)
\(\Leftrightarrow\left(3x-5\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}3x-5=0\\2x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}3x=5\\2x=-1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5}{3}\\x=-\dfrac{1}{2}\end{matrix}\right.\)
Vậy: \(x\in\left\{\dfrac{5}{3};-\dfrac{1}{2}\right\}\)
d) Ta có: \(\left(2x-1\right)^2-25=0\)
\(\Leftrightarrow\left(2x-1-5\right)\left(2x-1+5\right)=0\)
\(\Leftrightarrow\left(2x-6\right)\left(2x+4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-6=0\\2x+4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
Vậy: \(x\in\left\{3;-2\right\}\)
a: 49x^2-25=0
=>(7x-5)(7x+5)=0
=>7x-5=0 hoặc 7x+5=0
=>x=5/7 hoặc x=-5/7
b: Đề thiếu vế phải rồi bạn
c: (3x-2)^2-9(x+4)(x-4)=2
=>9x^2-12x+4-9(x^2-16)=2
=>9x^2-12x+4-9x^2+144=2
=>-12x+148=2
=>-12x=-146
=>x=146/12=73/6
d: x^3-6x^2+12x-8=0
=>(x-2)^3=0
=>x-2=0
=>x=2
e: x^3-9x^2+27x-27=0
=>(x-3)^3=0
=>x-3=0
=>x=3
a) \(-25+49x^2=0\)
\(\Leftrightarrow49x^2-25=0\)
\(\Leftrightarrow\left(7x\right)^2-5^2=0\)
\(\Leftrightarrow\left(7x-5\right)\left(7x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}7x-5=0\\7x+5=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}7x=5\\7x=-5\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5}{7}\\x=-\dfrac{5}{7}\end{matrix}\right.\)
b) \(16x^2-25\left(x-2\right)^2=0\)
\(\Leftrightarrow\left(4x\right)^2-\left[5\left(x-2\right)\right]^2=0\)
\(\Leftrightarrow\left(4x-5x+10\right)\left(4x+5x-10\right)=0\)
\(\Leftrightarrow\left(10-x\right)\left(9x-10\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}10-x=0\\9x=10\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=10\\x=\dfrac{10}{9}\end{matrix}\right.\)
c) \(\left(3x-2\right)^2-9\left(x+4\right)\left(x+4\right)=2\)
\(\Leftrightarrow9x^2-12x+4-9\left(x^2+8x+16\right)=2\)
\(\Leftrightarrow9x^2-12x+4-9x^2-72x-144=2\)
\(\Leftrightarrow-84x-140=2\)
\(\Leftrightarrow-84x=142\)
\(\Leftrightarrow x=-\dfrac{142}{84}\)
\(\Leftrightarrow x=-\dfrac{71}{42}\)
d) \(x^3-6x^2+12x-8=0\)
\(\Leftrightarrow x^3-3\cdot2\cdot x^2+3\cdot2^2\cdot x-2^3=0\)
\(\Leftrightarrow\left(x-2\right)^3=0\)
\(\Leftrightarrow x-2=0\)
\(\Leftrightarrow x=2\)
e) \(-27+27x-9x^2+x^3=0\)
\(\Leftrightarrow x^3-9x^2+27x-27=0\)
\(\Leftrightarrow\left(x-3\right)^3=0\)
\(\Leftrightarrow x-3=0\)
\(\Leftrightarrow x=3\)
\(a,\Leftrightarrow\left(x+3\right)\left(x+3-x+3\right)=0\Leftrightarrow x=-3\\ b,\Leftrightarrow x=0\left(x^2+4>0\right)\)
\(a,x^2+2.x.3+3^2-\left(x^2-3^2\right)=0\)
\(x^2+6x+9-x^2+9=0\)
\(6x+18=0\)
\(6x=-18\)
\(x=-3\)
Vậy x=-3
\(b,5x^3+20x=0\)
\(5x\left(x^2+4\right)=0\)
\(Th1:5x=0=>x=0\)
\(Th2:x^2+4=0\)
\(x^2=-4\)(vô lý)
Vậy x=0
a: Ta có: \(\left(3x+5\right)^2-4x^2=0\)
\(\Leftrightarrow\left(3x+5+2x\right)\left(3x+5-2x\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=-5\end{matrix}\right.\)
\(a,\Rightarrow x^2\left(5x-2\right)-\left(5x-2\right)=0\\ \Rightarrow\left(x-1\right)\left(x+1\right)\left(5x-2\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=1\\x=-1\\x=\dfrac{2}{5}\end{matrix}\right.\\ b,\Rightarrow2x\left(3x-5\right)+6x-10=0\\ \Rightarrow2x\left(3x-5\right)+2\left(3x-5\right)=0\\ \Rightarrow\left(2x+2\right)\left(3x-5\right)=0\\ \Rightarrow2\left(x+1\right)\left(3x-5\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=-1\\x=\dfrac{5}{3}\end{matrix}\right.\)
Lời giải:
a. $x^2-100x=0$
$\Leftrightarrow x(x-100)=0$
$\Rightarrow x=0$ hoặc $x-100=0$
$\Leftrightarrow x=0$ hoặc $x=100$
b.
$x^2+5x+6=0$
$\Leftrightarrow (x^2+2x)+(3x+6)=0$
$\Leftrightarrow x(x+2)+3(x+2)=0$
$\Leftrightarrow (x+2)(x+3)=0$
$\Leftrightarrow x+2=0$ hoặc $x+3=0$
$\Leftrightarrow x=-2$ hoặc $x=-3$
a) (3x – 5)2 – (x +1 )2 = (3x – 5 – x – 1)(3x – 5 + x + 1)
= (2x – 6)(4x – 4) = 8(x – 1)(x – 3)
Vậy (x – 1)(x – 3) = 0 ⇒ x - 1 = 0 hoặc x - 3 = 0
⇒ x = 1hoặc x = 3
b)(5x – 4)2 – 49x2 = (5x – 4)2 – (7x)2 = (5x – 4 – 7x)(5x – 4 + 7x)
= (12x – 4)(-2x – 4) = -8(3x – 1)(x + 2)
Vậy (3x – 1)(x + 2) = 0 ⇒ 3x - 1 = 0 hoặc x + 2 = 0
⇒ x = 1/3 hoặc x = -2
(3x-5)2-(x+1)2=0
<=> (3x-5-x-1)2=0
=>3x-5-x-1=0
<=> 2x-6=0
<=>2x=6
=>x=3 Vậy x=3